Designing Brand Identity FOT “KAE NOI” Green Products from Ethnic Groups through the Utiliztion of Cape Gooseberry Processed Items - Pudjaiyo Nunticha, Pongwiritthon Kajornatthapol, Kamchai Kamolthip Sawetrattanakul Sakollawat, Suttipong Thumtheang; Chavalit Honglertsakul (Journal of International Crisis and Risk Communication Research, 2024)
Purpose: The aim is to develop a prototype for branding 'Kae Noi' Green Products from ethnic groups. Theoretical framework: Qualitative research design was employed to investigate branding concepts and generate project ideas. Semi-structured interviews and workshops were utilized for data collection and assessing variables related to the research question. Sessions were aligned with study objectives, drawing insights from sources like Brand Development (Raza, Salleh & Shaari, 2021) and Branding and Packaging (Keller, K. L., 2013). Brand, branding, and packaging: Integral to Cape Gooseberry Processed Products' brand success, a well-established brand communicates unique value and identity, fostering consumer trust and loyalty. Branding involves analyzing strengths and weaknesses, creating a robust brand image, and adapting to evolving consumer behavior and market competition. Packaging plays a vital role in product design, facilitating distribution, transportation, and capturing consumers' attention, blending science and art for a satisfactory consumer experience. Design/methodology/approach: The study focused on crafting a brand identity for "Kaenoi" green products from fruit and vegetable growers associated with the Royal Project Kae Noi Agricultural Cooperatives. Diverse sampling techniques and in-depth interviews were utilized, ensuring accuracy and relevance in formulating a comprehensive brand concept, contributing to the economic and social well-being of ethnic communities. Findings: The brand design highlights the unique attributes of ethnic community goods, effectively conveying premium quality and fostering brand recognition. Packaging design sets the brand apart, affirming its distinctiveness and enhancing market competitiveness. Digital marketing strategies broaden distribution channels and contribute to commercial success. Practical & Social implications: Emphasizing unique identity, premium value, distinctive packaging, digital marketing, and cultural significance enhances market acceptance and differentiation from competitors, ensuring the success of Cape Gooseberry processed products under the "Kae Noi" Green Products brand. Originality/value: The brand design adds significant value by creating a unique identity, highlighting premium quality and cultural significance, contributing to market acceptance and differentiation.